Internal and External Factors that Influence Non-Performing Financing in Sharia Commercial Banks - Anindita, Kurniasih Setya; Tubastuvi, Naelati; Purwidianti, Wida; Kharismasyah, Alfato Yusnar (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
Problematic financing is reflected in Non-Performing Financing (NPF) because NPF is a parameter that can determine whether there is risky financing in Islamic banking. This research aims to determine the impact of Capital Adequacy Ratio (CAR), Operating Expenses and Operating Income (BOPO), inflation, and Bank Indonesia (BI) rates on Non-Performing Financing (NPF) in Sharia Commercial Banks in Indonesia. The data in this research uses secondary data. The population used is Sharia Commercial Banks registered with the Financial Services Authority (FSA) in 2018-2022. The sample used is the published report for the 2018-2022 quarter I-IV period. The research results show that BOPO has a positive and significant impact on NPF. Meanwhile, CAR, inflation, and BI rates have no significant impact on NPF.